Single‐cell transcriptomics reveals pathogen interactions and T cell reprogramming in HIV and Mycobacterium tuberculosis co‐infection - Zhao, Zihui; Huang, Suyue; Huang, Wei; Song, Wei; Liu, Li; Chen, Jun; Zhang, Renfang; Shen, Yinzhong (Frontiers in Immunology, 2025)
BackgroundHuman immunodeficiency virus (HIV) and Mycobacterium tuberculosis (Mtb) co-infection remains a major cause of mortality in AIDS patients, yet the mechanisms of pathogen interplay and host immune remodeling remain poorly understood. MethodsTo capture early untreated states, we applied single-cell RNA sequencing (scRNA-seq) to peripheral blood mononuclear cells from healthy controls, and from participants newly diagnosed with HIV mono-infection or HIV-Mtb co-infection, before therapy initiation. Integration guided by a Directed Acyclic Graph (DAG) inferred a pseudo-temporal trajectory from health to HIV infection to co-infection.ResultsAlong this continuum, TNF-α and TGF-β signaling progressively declined in CD8+ T cells and monocytes. Th1 cells emerged as the dominant anti-tuberculosis effectors, whereas Th17 cells exhibited transcriptional exhaustion and ribosomal stress signatures consistent with a non-responsive state. Cell communication analysis revealed fewer overall interactions but increased signaling strength within pathways during co-infection. Notably, we observed a transition in T cell from MHC class II to class I, a shift that was most pronounced in the CD4+ effector memory subset. These rewired interactions featured selective upregulation of inhibitory checkpoint molecules (PGE2–PTGES3–PTGER2/4, PPIA-BSG, PECAM1) and loss of stimulatory signals (CD6-ALCAM, CLEC2B/C/D-KLRB1). DiscussionOur study provides a single-cell roadmap of HIV-Mtb co-infection and identifies Th1/Th17 imbalance and MHC-I-biased T-cell signaling reconfiguration as candidate targets for restoring immune homeostasis.